The reality of strategic management and its relationship to empowering workers in the General Administration of Education in Asir Region - Asiri, Saleha Ibrahim Musa; AbdelKhair, Asia Jacob AlHadi (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the reality of strategic management and its relationship to empowering workers in the General Administration of Education in Asir region. The study used the descriptive analytical approach, In the General Administration of Education in Asir Region, came with a total average of (3.81 out of 5), that is, with a (significant) degree. As for the degree of administrative empowerment among its employees, it obtained an overall average of (3.78 out of 5), i.e. (high). The results also showed that there was a positive direct relationship amounting to (0.89) with statistical significance at (0.05) between strategic management and empowerment of workers in the General Administration of Education in the Asir region. And developing their creativity spirit, in addition to proposals for future studies on the subject.